2015
DOI: 10.18178/ijke.2015.1.3.033
|View full text |Cite
|
Sign up to set email alerts
|

Ontology Design for Thailand Travel Industry

Abstract: Abstract-Tourism industry plays a crucial role in the economics growth in countries of South East Asia and hence the demand for rich local tourist information for visitors. In these countries, there are unique deciding impact factors to visitor journey such as constraints in culture, laws, and festivals. Such special information has not been available or implemented in general search engines so far. In this paper, we design an ontology for Thai travel industry to support an intelligent finding of these local e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Most people infer the overall meaning based on both the direct and indirect meaning of words. I have concluded that all scenarios should be categorized in the pattern of ontology (Tantisripreecha & Soonthornphisaj, 2010;Saengsupawat, 2014;Wijasika & Srivihok, 2014;Khruahong, 2015;Tungkwampian, 2015). An especially interesting phenomenon is taboo words.…”
Section: Discussion and Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most people infer the overall meaning based on both the direct and indirect meaning of words. I have concluded that all scenarios should be categorized in the pattern of ontology (Tantisripreecha & Soonthornphisaj, 2010;Saengsupawat, 2014;Wijasika & Srivihok, 2014;Khruahong, 2015;Tungkwampian, 2015). An especially interesting phenomenon is taboo words.…”
Section: Discussion and Implementationmentioning
confidence: 99%
“…Additionally, our aim is to develop the cross-scenarios into a kind of ontologya term from computer science focused on the study of words' meanings. Several previous studies have confirmed that the cross-scenarios employed by semantic theory are effective regarding language-processing development (Tantisripreecha & Soonthornphisaj, 2010;Saengsupawat, 2014;Wijasika & Srivihok, 2014;Khruahong, 2015;Tungkwampian, 2015).…”
mentioning
confidence: 82%